How cost-effective is biofortification in combating micronutrient malnutrition? an Ex ante assessment - Meenakshi, J.V.; Johnson, Nancy L.; Manyong, Victor M.; DeGroote, H.; Javelosa, J.; Yanggen, D.R.; Naher, F.; González, C.; García, J.; Meng, E. (Elsevier, 2010)
Biofortification is increasingly seen as an additional tool to combat micronutrient malnutrition. This paper estimates the costs and potential benefits of biofortification of globally important staple food crops with provitamin A, iron, and zinc for twelve countries in Africa, Asia, and Latin America. Using a modification of the Disability-Adjusted Life Years framework we conclude that overall, the intervention can make a significant impact on the burden of micronutrient deficiencies in the developing world in a highly cost-effective manner. Results differ by crop, micronutrient, and country; and major reasons underlying these differences are identified to inform policy.